Phraseo-Semantic Field in the Uzbek Language - Jumaqulova, Shaxnoza (The Lingua Spectrum, 2025)
This article presents a systematic investigation of the composition, structure, and semantic characteristics of the phraseo-semantic field in the Uzbek language. The study aims to identify the mechanisms through which phraseological units are formed according to semantic groupings, as well as to determine their distribution into semantic layers consisting of the core, center, and periphery. Through a structural-semantic analysis, the research reveals the principles of semantic cohesion in Uzbek phraseological expressions that contain lexemes associated with the meaning of “joy.” The findings demonstrate that the phraseological system of the Uzbek language functions as a complex semantic structure organized around meaning fields.